Compact MoCA: A shortened alternative for MCI screening among healthy aging individuals. (31st December 2021) - Muadmanee, Wisawin; Hiransuthikul, Akarin; Chunharas, Chaipat; Thongkam, Achitpol; Petchlorlian, Aisawan; Praditpornsilpa, Kearkiat
Abstract: Background: The increasing number of elderlies highlights the important of clinical screening for cognitive impairment in healthcare setting. Montreal Cognitive Assessment (MoCA) is a widely used tool for mild cognitive impairment (MCI) screening, particularly among resource‐limited settings. Although originally claims to be a time‐saving tool of approximately 10 minutes, it takes much longer in real‐world settings, which consequently led to lack of MCI screening in many busy clinic settings. In order to shorten the duration for testing, we aimed to determine the performance of a compact MoCA which excludes domain(s) that does not correlate well with the total score. Method: Data of Thai healthy adults aged ≥60 years from a prospective cohort conducted in King Chulalongkorn Memorial Hospital, a tertiary care center in Bangkok, Thailand was included. MoCA was used to assess cognitive performance. Cognitive domain that showed poor correlation to the total score was excluded to build a compact MoCA in order to shorten the time of assessment. Sensitivity, specificity, and area under the receiver operating characteristic curve (AUROC) were used to evaluate the performance of the compact MoCA. Result: A total of 2, 799 participants who completed MoCA were enrolled. Correlation analysis showed that naming and orientation had the lowest degree of correlation to the total MoCA score (coefficients of 0.355 and 0.364, respectively) and delayed recall had the highest degree of correlation (coefficients of 0.609). After excluding naming, MoCA showed 100% sensitivity and 96.05% at a cut‐off score of 25. After excluding orientation, MoCA showed 100% sensitivity and 97.60% specificity at a cut‐off score of 19. After excluding both naming and orientation, MoCA showed 100% sensitivity and 93.4% specificity at a cutoff score 16. AUROC of MoCA after excluding naming, orientation, and both naming and orientation was 0.996, 0.998 and 0.994, respectively. Conclusion: The compact MoCA which excludes either naming or orientation showed great performance with 100% sensitivity and >95% specificity, suggesting a possible alternative method to shorten the duration for MCI screening while maintaining the quality of the test. An on‐going MCI screening using an electronic MoCA is on‐going to precisely assess time use per each domain.